The The Effectiveness of Election Supervisory Board’s Authority In Handling Election Administrative Violations: A Fiqih Siyāsah Perspective - Ahmad Hamzah; Nurnazli (Indonesian Journal of Law and Syariah, 2026)
This study aims to analyse the effectiveness of the authority of the General Election Supervisory Agency (Bawaslu) of Bandar Lampung City in handling administrative violations during the general election, and to examine its appropriateness from the perspective of political jurisprudence. This study employs a qualitative, descriptive-analytical approach through interviews, observations, and document analysis. The theoretical framework used includes the theory of authority implementation, as well as principles in siyasah tanfidhiyyah, particularly al-‘adl (justice) and maslahah mursalah (public interest). The research findings indicate that the Bandar Lampung City Election Supervisory Board (Bawaslu) is relatively effective in exercising its authority, particularly in preventing and addressing administrative election violations. This effectiveness is reflected in Bawaslu’s ability to actively identify and uncover violations whether through direct oversight or public reports and to follow up on them through recommendations to the General Election Commission (KPU). Furthermore, Bawaslu plays a strategic role in safeguarding the integrity of the election through a systematic process for handling violations, oriented toward upholding electoral justice. From the perspective of political jurisprudence (fiqh siyasah), the exercise of Bawaslu’s authority is consistent with the principles of al-‘adl and maslahah mursalah, which hold the government accountable for upholding justice and promoting the public interest. Thus, Bawaslu’s practice of supervising and enforcing election administration law can be viewed as consistent with Islamic legal values and as contributing to the maintenance of the rule of law within Indonesia’s constitutional system.